2016
DOI: 10.3389/fphar.2016.00391
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of CXCR2 Protects against Cigarette Smoke-Induced Lung Inflammation and Injury

Abstract: Antagonism of CXCR2 receptors, predominately located on neutrophils and critical for their immunomodulatory activity, is an attractive pharmacological therapeutic approach aimed at reducing the potentially damaging effects of heightened neutrophil influx into the lung. The role CXCR2 in lung inflammation in response to cigarette smoke (CS) inhalation using the mutant mouse approach is not known. We hypothesized that genetic ablation of CXCR2 would protect mice against CS-induced inflammation and DNA damage res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…54 Several previous inflammatory disease model studies showed that blocking or eliminating CXCR2 + cells is highly effective in reducing excessive leukocyte recruitment to inflammation sites. 18,19 Remarkably, Ly6C + macrophage numbers were higher in the inflamed joints. These cells are most likely recently accumulated to the joints in response to inflammation and are derived from circulating Ly6C + monocytes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…54 Several previous inflammatory disease model studies showed that blocking or eliminating CXCR2 + cells is highly effective in reducing excessive leukocyte recruitment to inflammation sites. 18,19 Remarkably, Ly6C + macrophage numbers were higher in the inflamed joints. These cells are most likely recently accumulated to the joints in response to inflammation and are derived from circulating Ly6C + monocytes.…”
Section: Discussionmentioning
confidence: 96%
“…16,17 Several inflammatory disease model studies showed that blocking or eliminating CXCR2 + cells is highly effective in reducing excessive leukocyte recruitment to the sites of inflammation. 18,19 The role of this receptor in regulating neutrophil recruitment is now better established using CXCR2 knockout strategies. 10 Indeed, CXCR2-deficient mice show impaired neutrophil recruitment into the peritoneal cavity, 20 lung, 21 and the skin.…”
Section: Introductionmentioning
confidence: 99%
“… 37 Further studies demonstrated that knockout of CXCR2, a receptor of IL-8, protected mice from cigarette smoke-induced lung inflammation and DNA damage in COPD pathogenesis. 38 …”
Section: Introductionmentioning
confidence: 99%
“…CXCL8 has been considered as an essential chemokine for neutrophil activation and recruitment. Blocking the binding of CXCL8 to its receptors, CXCR1/2, can effectively limit neutrophils recruitment and slow down inflammatory response 34,35 . In this study, the relationship between CXCR1/2 and swine pneumonia were determined using Real-Time PCR and immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%